2007
DOI: 10.29173/slw6962
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Understanding of Teacher and Librarian Collaboration (TLC)

Abstract: Teacher and librarian collaboration (TLC) is considered essential to support the changing population of students, complexity of educational issues, and increased information. However, collaboration has yet to be clearly defined for teachers and librarians. This article discusses four models of teacher and librarian collaboration (TLC) previously proposed by the author (Model A: Coordination, Model B: Cooperation, Model C: Integrated Instruction and Model D: Integrated Curriculum) and identifies five constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A theoretical model was proposed, distinguishing cooperation (least structured and formalized), coordination, and collaboration (most structured and formalized). Montiel-Overall (2017) discussed collaboration between teachers and librarians as "a trusting, working relationship between two or more participants involved in shared thinking, shared planning and shared creation of innovative integrated instruction" (2017, p. 260). Kammer and Moreland (2020) similarly used the term collaboration to describe mutual relationships between schools and public libraries.…”
Section: Conceptualization Of Collaboration and Partnershipsmentioning
confidence: 99%
“…A theoretical model was proposed, distinguishing cooperation (least structured and formalized), coordination, and collaboration (most structured and formalized). Montiel-Overall (2017) discussed collaboration between teachers and librarians as "a trusting, working relationship between two or more participants involved in shared thinking, shared planning and shared creation of innovative integrated instruction" (2017, p. 260). Kammer and Moreland (2020) similarly used the term collaboration to describe mutual relationships between schools and public libraries.…”
Section: Conceptualization Of Collaboration and Partnershipsmentioning
confidence: 99%
“…Findings from this research suggested that one of the most important factors is administrative involvement. Montiel-Overall (2005) stated that when the administrator is involved, the teacher-librarian and the class teacher truly collaborate. Haycock (2007) reported that school climate and time for planning were two important factors for joint planning, along with professional knowledge about the curriculum, library resources, instructional design, and delivery.…”
Section: The Practices Of Teacher-librarian and Teacher Collaborationmentioning
confidence: 99%
“…Considerable anecdotal and empirical information exists about conditions for collaboration (Mattissech & Mosner, 1992), best practices for collaboration (Falwell, 1998), environmental conditions that improve teacher and librarian collaboration such as flexible schedules (Rowe, 2007), characteristics of successful collaboration (Callison, 1997), levels of collaboration (Loertscher, 1988(Loertscher, , 2000Montiel-Overall, 2005, 2008, and innovation and creativity resulting from collaboration (Doll, 2005;Farmer, 2007). However, almost no information is available about educators' awareness of the role of librarians as collaborative partners in developing and implementing curriculum.…”
Section: Problem Statementmentioning
confidence: 99%
“…An extensive body of literature on teacher and librarian collaboration (TLC) has developed over the past twenty years (Bush, 2003;Callison & Morris, 1989;Copland & Messner, 2004;Doll, 2005;Haycock, 1999;Montiel-Overall, 2005, 2008a, 2008bOberg, 1995Oberg, , 1996Russell, 2002;Shannon, 2009). Information exists on best practices for collaboration including environmental conditions, flexible schedules (Gavigan, Pribesh & Dickinson, 2010), on principal support (Farmer, 2007;Morris, 2007;Oberg, 1995Oberg, , 1996Shannon, 2009), on characteristics of successful collaboration (Kim & Ju, 2008), on time considerations (Callison, 2006), on levels of collaboration (Loertscher, 1988(Loertscher, , 2000Montiel-Overall, 2005, 2008a, 2008b, and on characteristics of highly collaborative teachers and librarians (Bush, 2003;Montiel-Overall, 2008a). The literature on teacher and librarian collaboration indicates that sharing knowledge and information can maximize time, materials, and expertise (Callison & Preddy, 2006).…”
Section: Teacher Librarian Collaborationmentioning
confidence: 99%
See 1 more Smart Citation